2006
DOI: 10.2471/blt.05.028332
|View full text |Cite
|
Sign up to set email alerts
|

Development knowledge and experience - from Bangladesh to Afhanistan and beyond

Abstract: ProblemIn Afghanistan the challenges of development are daunting, mainly as a result of many years of conflict. The formation of a new government in 2001 paved the way for new initiatives from within and outside the country. BRAC (formerly Bangladesh Rural Advancement Committee), a Bangladeshi nongovernmental organization with a long history of successful work, extended its development model to Afghanistan in 2002. Local setting Provincial Afghanistan. Approach BRAC has implemented programmes in Afghanistan in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…The injection safety practices indicators were also comparatively better in Dhaka. This may be due to the fact that there had been a few previous interventions implemented to reduce misuse and promote safe injection practices in the selected UHCs of Dhaka [ 12 , 13 ]. The authors of the study with the funding support from the WHO/SIGN project implemented MTP intervention in 2004/2005 in 4 UHCs (these 4 UGCs were also included in our current study) of Dhaka.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The injection safety practices indicators were also comparatively better in Dhaka. This may be due to the fact that there had been a few previous interventions implemented to reduce misuse and promote safe injection practices in the selected UHCs of Dhaka [ 12 , 13 ]. The authors of the study with the funding support from the WHO/SIGN project implemented MTP intervention in 2004/2005 in 4 UHCs (these 4 UGCs were also included in our current study) of Dhaka.…”
Section: Discussionmentioning
confidence: 99%
“…A recent intervention study using monitoring-training-planning (MTP) strategy (an intervention which combines managerial, educational and regulatory strategies)[ 4 ] showed that the intervention has reduced the use injections in some health complexes in Bangladesh [ 13 ]. The intervention results are only indicative rather than confirmatory owing to lack of proper expertise, trained personnel, funding and sound methodology; and a small sample size in limited study areas.…”
Section: Introductionmentioning
confidence: 99%
“…By many accounts, BRAC is the largest NGO in the world. Its vast network of staff provides services to >110 million people in multiple countries 52. Despite being independently operated, BRAC has achieved nationwide program expansion more sustainably and with fewer management challenges than many of the government‐led programs cited above.…”
Section: Community Health Worker Program Scalabilitymentioning
confidence: 99%
“…Female CHVs, or Shasthya Shebikas , also sell health products such as contraceptives, iodized salt, ORS, safe delivery kits, sanitary napkins, and vegetable seeds with the support of microloan provisions from BRAC 11. Several other experimental cost‐recovery approaches are also being implemented at various BRAC sites that help motivate CHVs to provide high‐quality PHC services 52…”
Section: Community Health Worker Program Scalabilitymentioning
confidence: 99%
“…43 Across the world, regardless of the type of microfinance model used, loan repayment rates above 95% are common. [59][60][61][62] Below, we describe some of the models found in the literature.…”
Section: Methodsmentioning
confidence: 99%